INNOVATION AND INTERACTIVE METHODS IN THE EDUCATIONAL SYSTEM - Ro’ziyeva Nigora Ulug’bekovna (Лучшие интеллектуальные исследования, 2023)
Annotation: In this article, today's innovation and interactive in the educational system; Use of methods and its affective aspects detailed based on examples and substantiated. Especially in the modern educational system innovation or without interactive techniques, it is difficult to comfort the effectiveness of Education.